2018
DOI: 10.1108/ebhrm-12-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Voicing concerns for greater engagement

Abstract: Purpose Scholars argue that supervisor’s job insecurity may affect subordinates’ work engagement. Moreover, this relationship may be mediated by subordinates’ pro-social voice and the relationship between the supervisor’s job insecurity and subordinates’ pro-social voice may be moderated by organizational culture. Therefore, the purpose of this paper is twofold. First, to examine the mediating role of the subordinate’s pro-social voice between supervisor’s job insecurity and subordinates’ work engagement. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…3,4 A recent study found that individuals who raise their voice for innovative opinions and constructive suggestions are usually focused on their jobs and receive support from their leaders. 5 Despite the many advantages of voice behavior, there are obvious risks in raising one's voice, for instance, extraordinary personal stress, other employee's misunderstanding and interpersonal relationship issues. 6 As a result, the status quo of employee voice behavior and its contributing factors has become a research focus.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A recent study found that individuals who raise their voice for innovative opinions and constructive suggestions are usually focused on their jobs and receive support from their leaders. 5 Despite the many advantages of voice behavior, there are obvious risks in raising one's voice, for instance, extraordinary personal stress, other employee's misunderstanding and interpersonal relationship issues. 6 As a result, the status quo of employee voice behavior and its contributing factors has become a research focus.…”
Section: Introductionmentioning
confidence: 99%
“…); 5,792 (4.7%) participants were classified as “other” and 132 (0.11%) as administrative staff. Seven studies had unspecified samples (n = 2,609; 2.1%): Avgar et al ( 49 ) with 363 unspecified healthcare workers; Gupta and Ravindranath ( 66 ) with 1700 unspecified eye hospital employees; Hu and Casey ( 67 ) with 165 unspecified health care workers; Lawson et al ( 64 ) did not report sample size of participants (perfusionists); Lemke et al ( 68 ) did not specify on their sample of 49 anesthesia care providers; Mesdaghinia et al ( 69 ) reported a sample of 203 supervisors in a hospital; finally, Roussin et al ( 70 ) did not provide the numbers of nurses and physicians in their sample ( n = 129). Thus, based on the information provided, most of the participants were nurses (57.7% cumulative percentage of nurses, nurse managers and nurse experts).…”
Section: Resultsmentioning
confidence: 99%
“…With the feelings of being respected and valued, employees will accept the procedural decisions and outcomes, comply with organizational regulations, enhancing job engagement (Ramdeo and Singh, 2019). The concept of job engagement refers to the effort of employees (personal energy) in completing work tasks (Ramdeo and Singh, 2019), which requires both physical and psychological work participation (Gupta et al, 2018). Engaged employees are more enthusiastic and involved in their day-today-work.…”
Section: Procedural Justice and Ocb: Mediational Mechanismsmentioning
confidence: 99%